2013
DOI: 10.1656/045.020.0213
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Ecology of Fiddler Crabs,Uca pugnax, in Southern New England Salt Marsh Landscapes: Potential Habitat Expansion in Relation to Salt Marsh Change

Abstract: DISCLAIMER The o p i n i o n s and recommendations expressed i n t h i s r e p o r t a r e t h o s e o f t h e a u t h o r s and do n o t n e c e s s a r i l y r e f l e c t t h e v i e w s o f t h e U.S. F i s h and W i l d l i f e S e r v i c e , n o r does t h e m e n t i o n o f t r a d e names c o n s t i t u t e endorsement o r recom1983-19--. Species p r o f i l e s : l i f e h i s t o r i e s and e n v i r o n m e n t a l r e q u i r e m e n t s o f c o a s t a l f i s h e s and i n v e r t e b r a t e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 48 publications
1
17
0
Order By: Relevance
“…Luk and Zajac (2013) found Uca pugnax in the northeastern United States to be most common in low marsh, but not eroding seaward edges. Luk and Zajac (2013) found Uca pugnax in the northeastern United States to be most common in low marsh, but not eroding seaward edges.…”
Section: Generality Of Distribution and Abundance Patternsmentioning
confidence: 91%
See 1 more Smart Citation
“…Luk and Zajac (2013) found Uca pugnax in the northeastern United States to be most common in low marsh, but not eroding seaward edges. Luk and Zajac (2013) found Uca pugnax in the northeastern United States to be most common in low marsh, but not eroding seaward edges.…”
Section: Generality Of Distribution and Abundance Patternsmentioning
confidence: 91%
“…Luk and Zajac (2013) suggested that landward expansion of low marsh vegetation species may facilitate increased distribution of fiddler crabs. Luk and Zajac (2013) suggested that landward expansion of low marsh vegetation species may facilitate increased distribution of fiddler crabs.…”
Section: Crabs and Sea-level Risementioning
confidence: 99%
“…Fell et al (1982) found that the highest densities of U. pugnax occurred in bare areas alongside a mosquito ditch compared to vegetated habitat. Johnson (2014) observed that U. pugnax was rarely found in vegetated areas as opposed to non-vegetated habitats and Luk and Zajac (2013) stated that the highest abundances of U. pugnax were associated with bare ground patches in salt marshes of Long Island Sound. Finally, Ogburn and Alber (2006) reported heavy fiddler crab bioturbation in marsh dieback areas of Georgia, suggesting high numbers of crabs in open areas.…”
Section: Introductionmentioning
confidence: 99%
“…The total effect of M. pugnax , however, will be a product of its population‐level and per‐capita effects. For instance, the total impact of M. pugnax at the most northern site studied here (Rowely, Massachusetts) is likely small because their densities are substantially lower (1–6 m −2 ) (K. S. Martinez‐Soto & D. S. Johnson, unpublished data) than those at lower latitudes (60–120 m −2 ) (Culbertson et al, ; Luk & Zajac, ).…”
Section: Discussionmentioning
confidence: 93%
“…Minuca pugnax are ecosystem engineers (sensu Jones, Lawton, & Shachak, 1994) that modify marsh habitats through their burrowing activity and can indirectly influence a suite of saltmarsh functions. Minuca pugnax can stimulate aboveground plant biomass (Bertness, 1985), reduce belowground plant biomass (Gittman & Keller, 2013), enhance nutrient cycling and decomposition (Holdredge, Bertness, Herrmann, & Gedan, 2010;Thomas & Blum, 2010), change infaunal densities (DePatra & Levin, 1989), and affect sediment erosion or accumulation (Katz, 1980;Smith & Green, 2015 (Culbertson et al, 2007;Luk & Zajac, 2013).…”
Section: Consequences Of Body Sizementioning
confidence: 99%